Reaching disadvantaged groups through peers to improve health and nutrition behaviors in three districts of Nepal. - Pun, Bhim Kumari. (Tufts University. Tisch Library., 2016)
In her presentation, Ms. Pun seeks to understand whether peer mobilizers can make a difference in health and nutrition behaviors in disadvantaged groups. Delivered on Day 1 of the 2016 NIL Scientific Symposium in Kathmandu Nepal.; Nutrition School: NIL Symposium Presentations, 2016.; Accession Number: Bhim Kumari Pun-Reaching disadvantaged groups through peers to improve health and nutrition behaviors.pdf; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy